The Dyer's companion - Bemiss, Elijah (Dover Publications, 1973)
In 1806, when Bemiss's Dyer's Companion first appeared, the American dyeing industry was beset with problems; Europe was trying to maintain control of the market, and American dyers were often undertrained with recipes selling from master to apprentice "for twenty and thirty dollars each." To remedy this situation, Elijah Bemiss wrote his book. Today Bemiss's work is still important for seeing the exact methods of natural dyeing and understanding the life of the dyer in the early nineteenth century.